Cover Image, Volume 24, Issue 3. Issue 3 (14th February 2022) - Huh, Ki Young; Hwang, Jun Gi; Shin, Wonjung; BAEK, Seungjae; Choi, JaeDuk; Lee, Nora; Cho, Young Min; Lee, Howard
Abstract : The cover image is based on the Original Article A double‐blind, placebo‐controlled, single‐ascending dose study to evaluate the safety, tolerability, pharmacokinetics, and pharmacodynamics of HM15136, a novel long‐acting glucagon analogue, in healthy subjects by Ki Young Huh et al., https://doi.org/10.1111/dom.14590 .